Evaluation of the Formation Mechanism and Management of Reserve Components to Improve National Defense Economic: english - Saputro, Guntur Eko; Achmad, Irdham; Santoso, Totok Imam (Penerbit Goodwood, 2024)
Purpose: This study aimed to evaluate recruitment and training mechanisms of the formation and management of reserve components in national defense. Research methodology: The research method used is qualitative research with a case study design, which aims to obtain in-depth research results through data collection that contains meaning and can significantly influence the substance of a study based on a phenomenon. Result: Results Based on data collected through in-depth interviews, case studies, literature studies, and documentation.. Limitation: However, in the mobilization system, the coaching and supervision of reserve components are considered not to have achieved the realization and arrangement of the objectives that should be expected. Contribution: The findings and results of this study show that the management of reserve components in the initial preparation and formation has been carried out well.